2016
DOI: 10.3892/mmr.2016.4855
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin 1 protects astrocytes from oxidative stress by maintaining peroxiredoxin activity

Abstract: Previous studies have demonstrated that thioredoxin 1 (Trx1) exerts neuroprotective effects against cerebral ischemia/reperfusion injury caused by oxidative stress. While Trx1 is known to maintain the anti-oxidant activity of 2-Cys peroxiredoxins (Prdxs), the underlying mechanisms of its protective effects have remained to be elucidated, which was the aim of the present study. For this, an in vitro ischemic model of hypoxemia lasting for 4 h, followed by 24 h of reperfusion was used. Primary astrocytes from ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The AP-1 binding site within the SPATA12 core promoter (77–302 bp) encompasses the sequence 5′-TGAGTCA-3′, a core sequence in the AP-1 motif also known as the TPA responsive element (TRE) ( 22 ), is demonstrated in Fig. 4B .…”
Section: Resultsmentioning
confidence: 99%
“…The AP-1 binding site within the SPATA12 core promoter (77–302 bp) encompasses the sequence 5′-TGAGTCA-3′, a core sequence in the AP-1 motif also known as the TPA responsive element (TRE) ( 22 ), is demonstrated in Fig. 4B .…”
Section: Resultsmentioning
confidence: 99%
“…We showed that Tat-Trx1 protein transduced into HT-22 cells and markedly inhibited HT-22 cell death, ROS generation, and DNA fragmentation caused by oxidative stress. Recent studies have shown that knockdown of Trx1 can decrease astrocyte cell viability in an oxygen glucose deprivation/reperfusion (OGD/R)-induced cell model, suggesting that Trx1 can protect astrocyte cells from oxidative stress by exerting anti-oxidant effects ( Wang et al ., 2016 ). Overexpression of Trx1 protein can significantly protect against progressive β-cell failure in a T2DM animal model ( Stosic-Grujicic et al ., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that LPS can induce high levels of ROS and that antioxidants play a beneficial role against LPS-induced inflammation (52,53). It has been reported that Trx1 can protect cells against damage caused by oxidative stress in various diseases due to its anti-oxidant function (21,(54)(55)(56). In the present study, cell permeable fusion protein Tat-Trx1 transduced into macrophages and drastically reduced LPS-induced ROS generation and DNA damage, suggesting that Tat-Trx1 could play a beneficial role in cell survival against LPS-induced damage.…”
Section: Discussionmentioning
confidence: 99%